Ocena zaloge ogljika v načrtu trajnostnega gospodarjenja z gozdovi - Gačo Jež, Amina (Gozdarski vestnik, 2024)
Innovation plays an important role in EU rural development policy. One way of promoting innovation in the EU is through the establishment of Operational Groupings (OGs), which are part of the EIP-AGRI program. They bring together different stakeholders to promote innovation in agriculture and forestry. The FOREST4EU project promotes the different OGs in the EU countries and their innovations and organises them in five different Innovation Hubs (ITHubs). A total of 176 innovations from 86 OGs were identified, presented with extended summaries and prioritised in three steps (evaluation by project partners, by experts and at a workshop). In nine EU countries, a selection of the five most relevant innovations per ITHub was made (25 in total). In the case of Slovenia, Croatia, Latvia, and Portugal, one of the top-ranked innovations was the method for estimating the carbon stored in the woody biomass of forests for payments for ecosystem services of the GO FOR.TRACK Operational Group. This paper presents an innovative method for calculating the carbon stock based on forest biomass data that could be used to estimate the carbon stock in forest biomass and establish a voluntary market for emission credits. This is an innovation that could also benefit stakeholders in Slovenia.
Keywords: gospodarjenje z gozdovi; inovacije; inovacije v kmetijstvu in gozdarstvu; metoda za ocenjevanje ogljika, shranjenega v lesni biomasi gozdov; ogljični dobropisi; operativna skupina; plačilo za ekosistemske storitve; znanje